THE TERRITORIAL ORGANIZATION OF RURAL SETTLING OF POLTAVA REGION - Федій, Олександр (Human Geography Journal, 2014)
The study of rural settling in the region is important for its rational territorial organization and ensuring the quality of life of people in settlements. In the article the methodological approaches on highlighting of settling systems have been justified. The conducted analysis allowed highlighting rural settling systems in Poltava region and identify problems of their formation. It has been found out that the main production assets, social infrastructure objects, labor resource potential are concentrated in villages with management structures that contribute to their socio-economic development.